2009
DOI: 10.1007/s12149-009-0286-9
|View full text |Cite
|
Sign up to set email alerts
|

A bone marrow F-18 FDG uptake exceeding the liver uptake may indicate bone marrow hyperactivity

Abstract: The BM F-18 FDG uptake depends on the patient's age and serum CRP level, both with and without malignancy. A BM F-18 FDG uptake greater than or equal to that of the liver may indicate BM activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 24 publications
(33 reference statements)
2
75
1
1
Order By: Relevance
“…These data were concordant with the results of Inoue et al, who suggested that a FDG BMU greater than or equal to that of the liver indicates BM activation, and that the most likely cause is inflammation [29]. These results are also concordant with those previously reported at initial staging of Hodgkin lymphoma (HL), despite the fact that DLBCL is a less inflammation provider disease than HL [14].…”
Section: Discussionsupporting
confidence: 91%
“…These data were concordant with the results of Inoue et al, who suggested that a FDG BMU greater than or equal to that of the liver indicates BM activation, and that the most likely cause is inflammation [29]. These results are also concordant with those previously reported at initial staging of Hodgkin lymphoma (HL), despite the fact that DLBCL is a less inflammation provider disease than HL [14].…”
Section: Discussionsupporting
confidence: 91%
“…18 F]-FDG PET was not predictive of BM pathology [12,13,16,[19][20][21][22][23][24]. This is also our point of view and we believe that it should be ���������������������������������� MIP and axial images from a 35 year old male shows focal FDG uptake at the lower thoracic spine.…”
Section: Discussionmentioning
confidence: 91%
“…Discordant findings were associated to worse outcomes only if the BM biopsy (BM b ) was positive [13]. The utility of FDG PET-CT in evaluating BM involvement has also been explored by other authors with variable results as to its benefit [6,7,[12][13][14][15][16][17][18][19][20][21][22][23]. Because FDG PET-CT's are performed routinely now in the pretherapy staging of most lymphoma patients, extracting noninvasively additional information in regards to bone marrow status would be very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…There was mild and diffuse increase of FDG uptake in the bone marrow with a maximum standard uptake value of 2.5 in the spines, which was similar to the FDG uptake in the liver. According to a study by Inoue et al, 14 a bone marrow F-18 FDG uptake greater than or equal to that of the liver may indicate bone marrow hyperactivity. Therefore, bone marrow involvement could not be ruled out in this case.…”
Section: Discussionmentioning
confidence: 98%